Effect of Sophocarpine on the Pharmacokinetics of Umbralisib in Rat Plasma Using a Novel UPLC-MS/MS Method - Weng, Qinghua; Lan, Xia; Wang, Yingjie; Fan, Chen; Xu, Ren-ai; Zhang, Pengzhao (Frontiers in Pharmacology, 2022)
Umbralisib is a dual inhibitor of phosphatidylinositol 3-kinase delta (PI3Kδ) and casein kinase 1 epsilon (CK1ε) for treating marginal zone lymphoma (MZL) and follicular lymphoma (FL). This study aimed to develop a fast and stable ultra performance liquid chromatography tandem mass spectrometry (UPLC-MS/MS) method for quantitative analysis of umbralisib in rat plasma and its application for evaluating the effect of sophocarpine on the pharmacokinetics of umbralisib. A direct protein preparation with acetonitrile was used to deal with rat plasma. Umbralisib and internal standard (IS) were isolated on a Waters Acquity UPLC BEH C18 column (2.1 mm × 50 mm, 1.7 μm) and in the mixture of mobile phase A (acetonitrile) and mobile phase B (0.1% formic acid in water). Gradient elution with a flow rate of 0.40 mL/min was finally applied for quick separation. Positive ion mode and selective reaction monitoring (SRM) were set, and ion transitions for detection were at m/z 572.30→246.10 (umbralisib) and m/z 416.88→281.88 (IS), respectively. The excellent linearity with a wide concentration range was from 0.5 to 1000 ng/mL. Both of the precision (RSD%) and accuracy (RE%) were less than 15% in a permissible range. The mean recovery and matrix effect of umbralisib were 86.3-96.2% and 97.8-112.0%, respectively. When umbralisib was combined with sophocarpine, AUC0→∞ of umbralisib was significantly reduced to 2462.799 ± 535.736 ng/mL•h from 5416.665 ± 1451.846 ng/mL•h, and MRT and Cmax also markedly diminished. Moreover, Vz/F notably rose from 382.192 ± 158.076 L/kg to 587.055 ± 211.553 L/kg, and CLz/F increased more than two times. This developed, optimized and technical UPLC-MS/MS method was extremely suitable for detecting the plasmatic concentrations of umbralisib in rats after an oral administration, and sophocarpine had a significant inductive effect on the pharmacokinetics of umbralisib in rats. This obvious pharmacokinetic changes indicates that there seems to exist herb-drug interaction between sophocarpine and umbralisib.